Studi Komparatif Penerapan Model Pembelajaran Berbasis Masalah Dan Berbasis Proyek Terhadap Minat Belajar Dan Keterampilan Berpikir Kritis Siswa Kelas XII IPA SMA Negeri Sindue - Abdul Muluk; I Nengah Kundera; I Made Budiarsa (Universitas Tadulako, 2015)
This study aims to determine the student’s interest and critical thinking skills of the twelfth grade students of IPA at SMAN 1 Sindue through the application of problem based learning and project based learning. The study was conducted using an experimental method of pre-experimental design used one shot case study. The samples of this study were 34 students of class XII IPA 1 and 34 students of class XII IPA 2. The instrument used was student’s questionnaire test, assessment sheets of critical thinking, and observation sheets of teacher and student activities. Based on the analysis of the data obtained, the results are: through the application of problem-based learning and project-based learning of the twelfth grade students of SMAN 1 Sindue the student’s interest in learning was categorized as high. This is supported by the results of the research. There is no significant difference between the students' interestt who taught by using problem-based learning and project based learning. Both learning models are effectively contributes to increase student’s critical thinking skills with the result that there are significant differences between students' critical thinking skills of the twelfth grade students of IPA 1 and IPA 2 although both the mentioned group was categorized in the level of critical thinking.